A Time and Motion Study of Community Health Workers in Rural Area of Ballabgarh, Haryana - Suprakash Mandal; Ramadass Sathiyamoorthy; Harshal Ramesh Salve; Ravi Kumar; Rakesh Kumar (Indian Journal of Public Health, 2023)
Introduction: Health workforce is the important pillar of health system in India. Efficient utilization of scarce community-level human resources in health care is critical to ensure optimum care in a community. Objective: To describe the time utilization pattern of health workers (HWs) during field activity at the primary healthcare level and to study the facilitators and barriers in efficient time utilization. Methods: A mixed-method study with a time and motion approach was carried out in the rural areas of Ballabgarh block of Haryana. Time and motion approach was continuous, direct, synchronous and both active and passive method of time logging was adapted. Electronic Geo-Positioning System based mobile, timestamp application and the digital stopwatch were used to capture time utilization. The quality of the data collected in the daily work plan during the household (HH) visits was assessed using semi-structured interview schedule. In-depth interview with the HWs was carried out to understand the facilitating factors and barriers in their efficient functioning. Results: Proportion of HH s covered in data collection for time and motion patterns was 36% out of the total number of HH s in the SCs. The completeness of work plan was 74.8%. The average number of HHs covered per day by an HW was 38. Mean (standard deviation [SD]) time duration spent in each HH in completing the work plan was 2.9 (0.8) minutes. Mean (SD) total distance travelled by HW per day was 1845.1 (974.2) metres. Mean (SD) time duration spent idle in the field was 22.7 (13.0) minutes. Proportion of effective time utilised in the field was 54.3%. Several enabling factors and barriers were identified at personal, community, and health system level. Conclusion: Only half of the allotted time was effectively utilized by the HWs for house visit in the community. Planning the beat schedule as per the feasibility and ensuring quality of HH visits using information technology is critical for providing primary healthcare at village level.